Witness of Faith: Homiletical Proposals and Evangelii Gaudium for the Homily - Stanislaus Alexander Noning; Leonardus Samosir (FOCUS, 2025)
This article aims to illustrate the contributions of homiletics, including the guidance found in Evangelii Gaudium, for the formulation of a homily. Research conducted in two parishes within the Bogor Diocese reveals the dynamics observed in the field regarding the expectations of a homily and the preparation undertaken by the homilist. The findings indicate that a homily transcends mere rhetoric within the liturgy; it represents an encounter of faith between the Word of God and the congregation, mediated by the homilist. This underscores the significance of the homilist's testimony of faith; a testimony that is cultivated in a prayerful atmospher, articulated in the language of the audience, and inspires the congregation towards transformation.